Influencia de la enteroparasitosis en el rendimiento escolar de alumnos del 4° grado de primaria de la I.E. “Ramón Castilla y Marquesado”. Iquitos 2023 - Ruiz Armas, Tomasa Orfilia (2024)
The objective of this research was to determine the influence of enteroparasitosis on the school performance of 4th grade primary school students at the I.E “Ramón Castilla y Marquesado”, the study is located within the descriptive-explanatory research and with a correlational design. . 126 schoolchildren participated, of whom stool samples were collected to determine the existence or not of intestinal parasites. A sociodemographic and individual characteristics sheet was also applied to the parents who signed the informed consent, on clinical manifestations of the students. who have accepted their participation through assent. The inferential statistical study used a significance of p < 0.05, 95% confidence and a margin of error of 5%. As results: it was observed that 4th grade primary school students from the I.E “Ramón Castilla y Marquesado” have a prevalence of parasitosis of 56%. The nematodes (Ascaris and Trichuris) were the ones with the highest percentage, 34%, followed by the protozoans (Giardia) with 16% and the lowest infestation was by Platyworms (Hemynolepis nana) with 6%., the school performance in the area Communication scores were 48% and 9% regular and deficient respectively. Likewise, in the discipline of mathematics, a good performance of 44% was achieved and 13% poor. Regarding overall performance, it is evident that 86.5% of students present good academic performance and 13.5% poor performance. It was concluded that students with enteroparasitosis have 80% without a deficient evaluation, that is, good or average, and 20% with at least one deficient evaluation in one of the areas of mathematics or communication. Therefore, the influence of enteroparasitosis on overall school performance is significant p= 0.017.